EXPLORING THE IMPACT OF LEADERSHIP STYLES ON EMPLOYEE JOB PERFORMANCE - A CASE STUDY OF EMPLOYEES IN VIETNAMESE ENTERPRISES - Lin, Linda Lin-Chin; Viet , Nguyen-Van (International Journal of Application on Economics and Business, 2025)
This study explores the impact of leadership styles on employee job performance in Vietnamese enterprises, focusing on authoritarian, democratic, and laissez-faire leadership styles. Through a questionnaire survey, 298 valid responses were collected and analyzed using SPSS 25.0, including descriptive statistics, reliability analysis, t-tests, ANOVA analysis, correlation analysis, and regression analysis.The findings indicate: (1) Authoritarian leadership has a significant negative impact on employee job performance; (2) Democratic leadership has a significant positive impact on employee job performance; (3) Laissez-faire leadership has a significant positive impact on employee job performance. This study emphasizes the flexible use of leadership styles to improve employee performance and suggests the reasonable application of democratic and laissez-faire leadership to foster responsibility and creativity among employees, ultimately enhancing company competitiveness and long-term growth.